English teacher collaboration: A key strategy for overcoming psychopedagogical challenges and promoting educational wellbeing - Rodriguez-Barboza, Jhonny Richard (2024)
In this study, the focus is on the collaborative efforts among English educators and their impact on the quality of teaching and learning. The central aim is to deeply explore this collaborative practice and its significance within today's educational landscape, underlining its capacity to navigate the diverse student population and the continuously evolving pedagogical hurdles. The primary objective is to thoroughly analyze how teacher collaboration influences the quality of teaching and learning. Employing a socio-critical qualitative approach, an extensive search for academic sources was conducted across various academic databases and digital libraries. The findings suggest that collaborative work among teachers has the potential to enhance student performance and foster teaching coherence. Nevertheless, there exist challenges such as time constraints and discrepancies in pedagogical methodologies. In conclusion, the pivotal role of teacher collaboration in education is underscored, particularly in adapting to modern challenges like the integration of technology in classrooms. Teacher collaboration serves as a conduit for enhancing educational quality and advancing equity, albeit acknowledging the imperative to address obstacles for more effective collaboration.